SURG-40. SURGICAL RESECTIONS IN BROCA'S AREA DO NOT LEAD TO BROCA'S APHASIA. (9th November 2020) - Andrews, John; Cahn, Nathan; Speidel, Benjamin; Lu, Valerie; Berger, Mitchel; Chang, Edward
Abstract: Brodmann's areas 44/45 of the inferior frontal gyrus (IFG), are the seat of Broca's area. The Western Aphasia Battery is a commonly used language battery that diagnoses aphasias based on fluency, comprehension, naming and repetition. Broca's aphasia is defined as low fluency (0-4/10), retained comprehension (4-10/10), and variable deficits in repetition (0-7.9/10) and naming (0-8/10). The purpose of this study was to find anatomic areas associated with Broca's aphasia. Patients who underwent resective brain surgery in the dominant hemisphere were evaluated with standardized language batteries pre-op, POD 2, and 1-month post-op. The resection cavities were outlined to construct 3D-volumes of interest. These were aligned using an affine transformation to MNI brain space. A voxel-based lesion-symptom mapping (VLSM) algorithm determined areas associated with Broca's aphasia when incorporated into a resection. Post-op MRIs were reviewed blindly and percent involvement of pars orbitalis, triangularis and opercularis was recorded. 287 patients had pre-op and POD 2 language evaluations and 178 had 1 month post-op language evaluation. 82/287 patients had IFG involvement in resections. Only 5/82 IFG resections led to Broca's aphasia. 11/16 patients with Broca's aphasia at POD 2 had no involvement of IFG in resection. 35% of IFG resections were associated with non-specific dysnomia and 36% were normal. By one-month, 76% of patients had normal speech. 80% of patients with Broca's aphasia at POD 2 improved to normal speech at 1-month, with 20% improved to non-specific dysnomia. The most highly correlated (P< 0.005) anatomic areas with Broca's aphasia were juxta-sylvian pre- and post-central gyrus extending to supramarginal gyrus. While Broca's area resections were rarely associated with Broca's aphasia, juxta-sylvian pre- and post-central gyri extending to the supramarginal gyrus were statistically associated with Broca's type aphasia when resected. These results have implications for planning resective brain surgery in these presumed eloquent brain areas.